Sb-doped Tl8.67 Sn1.33-xSbx Te6 nanoparticles improve power factor and electronic charge transport - Khan, Sabir; Shah, Wiqar H.; Tufail, M.; Ali, Akhtar; Eldin, Sayed M.; Imran, Naveed; Sohail, Muhammad (Frontiers in Materials, 2023)
Thallium telluride Tl8.67 Sn1.33-xSbxTe6 nano compound doped with different concentration ratios of Sb (x = 0.63, 0.65, 0.66, 0.68, 0.70, or 0.72) was prepared using solid-state techniques, and the compound was heated up to 550 K in vacuum silica tubes. The structure of the nano system was studied using XRD and EDX. It was confirmed that, without any other impurities, the nano system had a single-phase tetragonal crystal structure. The measured Seebeck coefficient (S) of all nano compounds showed that S increased with increase in temperature from 300 to 550 K. S was positive at all temperatures, showing characteristics of a p-type semiconductor. The complex behaviour of S in an Sb-doped nano system showed that at low temperature (room temperature), S first decreased with an increase in Sb concentration up to x = 0.65 and then increased with an increase in the Sb dopant up to x = 0.72. Similarly, electrical conductivity (σ) decreased with an increase in temperature, and the power factor showed complex behaviour relative to Sb concentration. The power factor observed for Tl8.67 Sn1.33-xSbx Te6 nano compound increased with an increase in temperature, within a temperature range of 300–550 K. Tellurides are semiconductors of very narrow band-gap, with component elements in common oxidation states, according to (Tl+9) (Sb3+) (Te2-)6. The phase range was also assessed, and results demonstrated that different Sb dopant ratios were associated with differences in properties (e.g., electrical, thermal, and Seebeck effect) and hence variation in power factor. These results indicate a route through which the thermoelectric characteristics of Tl8.67 Sn1.33-xSbxTe6-based nano materials were harnessed for the development of thermoelectric and electronic applications.